Teacher empowerment through engagement in a learning community in Ireland: working across disadvantaged schools. Issue 3 (27th May 2017) - Tannehill, Deborah; MacPhail, Ann
Abstract : This ongoing longitudinal study examined the professional development of physical education teachers in an Irish physical education learning community where all teachers worked in inner-city disadvantaged schools. This research is framed within teacher empowerment. Four years of data collection included in-service seminar/workshop evaluations, small group discussions and focus group and individual interviews. Data were analysed to allow us to answer three research questions that focused on support in setting and achieving group goals, shared experiences of planning and teaching students and the informed development of learning communities towards a community of practice model. Results highlight the support these teachers provide one another, the empowerment these teachers developed to address issues posed by their challenging work situations (e.g. limited facilities, low economic conditions, students with challenging behaviour) and the motivation that being a member of a community afforded them to persevere in teaching in difficult settings. This research is ongoing as we explore and examine how the same group of teachers are able to maintain the work of their community, reinvent themselves and move from concluding one phase to begin new projects and impact student learning.